The effect of IFRS adoption on accrual-based and real earnings management: Emerging markets' perspective - Viana, D. B. C., Jr.; Lourenço, I.; Paulo, E. (Journal of Accounting in Emerging Economies, 2023)
Purpose: This study analyzes the effect of the mandatory adoption of the International Financial Reporting Standards (IFRS) on the level of both accruals-based (AEM) and real earnings management (REM) in a comprehensive sample of firms from emerging markets. It also analyzes whether this effect differs depending on the nature/extent of IFRS adoption (full versus modified). Design/methodology/approach: Some previous studies predominantly made up of samples from developed countries suggest a substitution of AEM for REM in the post-IFRS period. The authors test whether this trade-off among the two earnings management strategies is also evident in emerging markets, based on a sample of 27,789 firm-year observations from 18 countries between 2000 and 2018. Findings: The results suggest that IFRS adoption in emerging markets is associated with the replacement of REM by AEM, unlike previous overall evidence in developed countries where firms appear to do the opposite. The results also show that this replacement is lower in the emerging markets fully applying IFRS, when compared to those applying a modified version of these international standards. Practical implications: Possibly due to the poor institutional environment of emerging markets, coupled with greater flexibility inherited of IFRS principles-based approach, the authors reiterate an imminent concern about IFRS encouraging substitution of REM for AEM in emerging countries, namely in those applying a modified version of IFRS. Originality/value: While the predominant IFRS literature in emerging markets remains focused on analyzing only single-country studies, promoting clearly mixed results, the authors enhance such discussion and foster this debate on a more international level by analyzing the joint effect of IFRS in 18 emerging markets and by comparing the effect of full and modified IFRS adoption.